Relating character to conduct violations at US service academies - Wood, Dustin; Giambra, Leonard M.; Mullaney, Kevin (Military psychology, 2025)
Military service academies hold the promotion and development of to be central to their mission, and institutional systems for identifying and penalizing instances of misconduct serve an important role toward this end. Here, we explore how items and scales within an early version of the Values in Action (VIA) instrument completed by several cohorts of cadets at the United States Naval Academy and United States Coast Guard Academy predicted their cumulative number of conduct offenses recorded while at the academy. At both academies, similar dimensions of the VIA predicted the number of conduct offenses committed by cadets: Self-Regulation, Modesty/Humility, and especially Prudence scales predicted fewer conduct offenses, whereas the Social Intelligence, Originality/Creativity, and Humor/Playfulness scales predicted more conduct offenses. Analysis of the 240 individual items of the VIA demonstrated significantly improved prediction of conduct offenses relative to the instrument's 24 broader scales. The results indicate a consistent profile of character attributes predicting the commission of conduct offenses at both service academies, and may be expected to predict levels of misconduct in other contexts.